(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Tumour is an alarming issue for pet animals, especially for dogs and cats. Mammary gland tumour is the most concerning type for pets after lymphoma and skin tumours. To know the clinical features in the mammary gland, size and stage of the tumour, growth and supply of lymphatic vessels and blood vessels ultrasonography is a useful diagnostic tool. Haematological examination for blood test measure is a classical way to identify the malignancy stage of tumour, which we used for our study. Initially, 10 dogs were proposed to conduct the study but different circumstances like a devastating flood in the greater Sylhet region ultimately delayed our working period. For these reasons, we conducted our study on 8 dogs. Among 8 examined dogs, two were found positive by ultrasonography using B-mode which implies a prevalence of 25% (2 out of 8). Several studies reported a high prevalence of mammary gland tumours in case of dogs. Lower prevalence according to our study, maybe because we examined stray dogs and they acquire strong natural immunity and Canine mammary gland tumours are less prevalent in dogs under the age of 5 years and the average age of dogs examined by our study was 1.875 years. To determine if there is any difference between the ultrasound positive and negative dogs, one sample t-test was done where test positive and test negative is the independent variable and all the blood parameters are the dependent variable and the blood parameters significantly vary (p-value< 0.001) between positive and negative animals. Again, using B-mode was not efficient enough to see the differences between malignant and benign tumours. However, the study result of this project can be used for baseline information of future similar studies. Further study should be conducted with higher age groups and sophisticated diagnostic tools. Res. Agric. Livest. Fish. Vol. 12, No. 1, April 2025: 53-62